Workshop Pembuatan Filter Air Sederahana untuk Pengelolaan Air Keruh di Desa Wibawamulya - Dini, Fathiyah Rahma; Juliandara, Luthpiyah; Qintharah, Yuha Nadhirah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Clean water is a basic necessity. In Wibawamulya Village, most water sources are cloudy and foul-smelling, failing to meet clean water standards. This situation affects the health and daily activities of the community, especially children. This community service program was carried out through a training workshop targeting elementary school children. The stages included observation, socialization, hands-on training, and evaluation. Materials used included used bottles, cotton, sponge, sand, gravel, and bio rings. Held on February 18, 2025, the training was attended by 8 participants. Children were able to understand the importance of clean water and create simple filters independently. The filtered water appeared much clearer, and evaluations showed improved knowledge and awareness. The program had a positive impact on children’s technical skills and environmental awareness. Weather constraints were overcome through good teamwork. This activity can be further developed through collaboration with government and relevant institutions.